Kinematic simulation of an excavator - Tan, Yong Jian (2014)
This is a project suggested by Singapore Technologies Kinetics and the main purpose is to build up the capability in performing simulation to determine the load case and finite element analysis to determine the stress value and correlate with the actual measured result. The scope of this is limited to the arm and boom of a crawler excavator. There are four main programs used in this project to attempt the tasks as stated, namely, Solidworks, Solidworks Motion, Unigraphics and ANSYS. The first and the third programs are computer-aided design programs used to ensure that the accuracy of the model and to modify the model for usage for force determination and finite element analysis. The second program is part of the Solidworks that focuses on the motion simulation of the excavator and the reaction forces acting on the excavator is obtained. The last program used is a finite element analysis program, which is used to determine the maximum principle stresses and the equivalent stresses acting on the arm and the boom depending on the different conditions. The results obtained from ANSYS is then compared with the physical data obtained and the main conclusion is that the difference between the results are reasonable at most locations. There are some locations whereby the results do not correlate very well. Suggestions on the locations where some problems exist will assist the company in looking into them and getting more data for an even more accurate analysis of the problem.